The level of satisfaction with nursing care among patients hospitalized in the Neurosurgery ward - Frankiewicz, Anna; Lelonek, Barbara (Polish Journal of Public Health, 2012)
Introduction. Patient satisfaction survey of hospital stay is a common method to assess quality of care. It is a valuable way to prevent iatrogenic errors, mistakes and verify the quality of medical services. Thanks to the surveys the therapeutic team obtains information on the level of care exercised by them, identifies the needs and expectations of the patients, and helps in solving their problems.Aim. The aim of this study was to assess patients’ satisfaction with nursing care in the neurosurgery ward in Provincial Hospital in Kielce.Material and methods. The work is an attempt to assess the level of satisfaction with medical care. The study was conducted in the Provincial Hospital in Kielce, in the Ward of Neurosurgery in the first half of 2010. The study involved 52 patients. They joined the study on a voluntary basis. The tool used in this study is a survey questionnaire by Helena Lenartowicz for evaluating patient’s satisfaction with nursing care.Conclusions. It was found that the level of satisfaction with nursing care in the Provincial Hospital in the Department of Neurosurgery is high. Patients are satisfied with the stay and the provided nursing care. Almost all of the respondents would recommend the hospital to their relatives and friends due to the high level of care. Nurses working in the Neurosurgery ward are very nice and friendly. Patients are informed of their rights while in hospital. During all nursing and therapeutic treatments privacy is guaranteed. The meals aren’t varied enough; they are tasteless and served in too different intervals. Religious and spiritual needs of patients hospitalized in the ward are provided almost to everyone (98%).